Protein palmitoylation: an emerging regulator of inflammatory signaling and diseases - Chen, Rong; Tang, Xiaohua; Wang, Ying; Wang, Bo; Mao, Fei (Frontiers in Immunology, 2025)
Protein palmitoylation is a reversible lipid modification in which palmitoyl esters are covalently attached to cysteine residues of proteins. It controls various cellular physiological processes and alters protein stability, conformation, localization, membrane binding, and interaction with other effector proteins. Palmitoylation is catalyzed by a group of zinc finger DHHC-containing proteins (ZDHHCs), while the acyl-protein thioesterase family mediates depalmitoylation. Emerging evidence suggests that palmitoylation is critical for inflammatory signaling pathways, where palmitoylation is particularly important in the membrane localization of inflammation-associated proteins. Notably, dysregulation of palmitoylation has been associated with a variety of inflammatory diseases. Here, we provide an overview of the regulatory mechanisms of palmitoylation, explore the emerging role of palmitoylation in inflammatory signaling pathways, and examine the link between dysregulated palmitoylation and the pathogenesis of inflammatory diseases, including inflammatory bowel disease, autoimmune diseases, metabolic dysfunction-associated steatohepatitis, sepsis, Alzheimer’s disease, Parkinson’s disease, and diabetes. Finally, we discuss some of the challenges and opportunities facing the field. Targeting palmitoylation or its associated enzymes serves as a novel therapeutic approach for the treatment of inflammatory diseases.